Legal Analysis of the Status of Song Copyright Royalties as Joint Assets in Divorce Proceedings (A Study of Judgement Number 1622/Pdt.G/2023/PA.JB) - Keisya Yvoni Riesvandha (Law Research Review Quarterly, 2026)
This study analyzes the status of copyright royalties for musical works as joint assets following divorce, based on the case in Judgment No. 1622/Pdt.G/2023/PA.JB. Methodology employed combines a normative legal approach with a literature review. The analysis demonstrates that copyright royalties can be classified as joint assets because they constitute ongoing income derived from works created during the marriage. A spouse who contributed to the creation of intellectual assets has the right to a share of the assets, even if they are not the rights holder. Although this is not explicitly provided for in copyright law, as seen in Judgment No. 1622/Pdt.G/2023/PA.JB, this does not preclude the possibility of dividing the royalties. In the proceedings of this case, the judge referred to theory distributive justice and ensured that the distribution of royalties was proportional and fair, based on the contributions and roles of each party within marital relationship. In accordance with the provisions of matrimonial law based on the Marriage Act, the Civil Code, and the Compilation of Islamic Law, the same result would apply when dividing copyright royalties as joint assets, with receiving half of the joint assets.